“Sowing the Seed of National Strife in This Alien Region”: The Pahlen Report and Pereselenie in Turkestan, 1908–1910 - Morrison, Alexander Stephen (My University, 2012)
This article examines the institutional background to the decision to send Senator Count K. K. Pahlen's Commission of Inspection to Turkestan in 1908. It concentrates on the divisive issue of 'pereselenie', or peasant resettlement, which Pahlen was supposed to be facilitating but ended up opposing. The article also seeks to establish the value or otherwise to the historian of the Pahlen Commission's multi-volume report.
Keywords: Imperial History; Central Asian Studies; Colonialism; Central Asia (History); Russian History